Development at 18th & Vine: understanding problems and formulating strategies for the future - Giesler, Cole (Kansas State University, 2009)
Redevelopment of the 18th and Vine neighborhood has long been a goal of community leaders in Kansas City. Through the redevelopment there is an opportunity to restore pride to an impoverished area once considered the center of black life in the city. During segregation the area around 18th and Vine was famous for its baseball, jazz, and nightlife. However, the area slowly fell into decay. Since the 1980s there has been a renewed focus on the redevelopment of the area with major additions including: museums, music clubs, restaurants, and space for retail. Difficulty in finding tenants for the new retail space has lead to an uncertainty about how to proceed with the development. Understanding the failure to attract retail space to the area is a potential guide for future successful development around 18th and Vine. Lessons learned from African American community development include the need to define the community accurately (Dorius 2009), utilize community organizations (Dorius 2009), encourage residential empowerment (Dorius 2009), create economic self-sufficiency (Moore 2005, Katz 2004), encourage middle class black migration (Sampson 2009), and limit the negative effects of gentrification (Kirkland 2008). These lessons along with information gained in the studies of Overtown in Miami, Florida and Beale Street in Memphis, Tennessee were applied to the information about 18th and Vine identifying issues associated with redevelopment of the community. New design strategies and guidelines were developed utilizing the understanding of why the area around 18th and Vine decayed and why new development has thus far failed. A combination of socio-economic and physical strategies is needed to make more informed decisions about future development. The physical strategies are proposed as alternative frameworks of focusing on the core, expanding to the south, and expanding to the west.
Keywords: 18th and Vine; African American Development; Black Development; Landscape Architecture (0390); Urban and Regional Planning (0999)